How We Manage Patients with Indolent B-Cell Malignancies on Bruton’s Tyrosine Kinase Inhibitors: Practical Considerations for Nurses and Pharmacists - Shannon Nixon; Dominic Duquette; Sarah Doucette; Jean-Francois Larouche (Current Oncology, 2023)
The most common forms of B-cell malignancy, non-Hodgkin lymphoma (NHL) and chronic lymphocytic leukemia (CLL), have seen a drastic shift in the treatment landscape over the last two decades with the introduction of targeted agents. Among them are Bruton’s tyrosine kinase (BTK) inhibitors, which have demonstrated excellent efficacy in indolent B-cell NHLs and CLL. Although BTK inhibitors are generally thought to be more tolerable than chemoimmunotherapy, they are associated with a unique safety profile including varying rates of rash, diarrhea, musculoskeletal events, cardiovascular events, and bleeding. Ibrutinib was the first BTK inhibitor to gain a Health Canada indication, followed by second-generation BTK inhibitors acalabrutinib and zanubrutinib, which have better safety profiles compared to ibrutinib, likely due to their improved selectivity for BTK. As BTK inhibitors are oral agents given continuously until disease progression, long-term adverse event (AE) monitoring and management as well as polypharmacy considerations are important for maintaining patient quality of life. This paper intends to serve as a reference for Canadian nurses and pharmacists on dosing, co-administration, and AE management strategies when caring for patients with indolent B-cell NHL or CLL being treated with BTK inhibitors.